IMPACT OF MOVIE ON THE YOUNG VIEWERS' REPRESENTATIONS OF SENIOR PEOPLE - Tina A Kubrak; Taisiya A Grebenschikova (Peoples' Friendship University of Russia (RUDN University), 2018)
Cinema, as one of the most influential mass media, plays an important role in the life of the modern society, being a very popular leisure activity. Movies have effects on the audience's motivation, values, stereotypes, activities and mental representations of reality. The current study is devoted to the problem of the movie impact on the young audience. The various effects of the movies about senior people on the young viewers' corresponding representations are discussed. The psychosemantic method was used to measure the emotional, regulative and cognitive personal traits of both perceived senior and young people. The measurement includes 25 scales designed particularly for eliciting the representations of senior people by the young audience. The viewers scaled seniors' personal traits before, right after and two weeks later after watching the movie. Also they scaled themselves as being seniors in the future. Such variables as gender, attractiveness of the movie and the place of movies in leisure were taken into account. The film affected the representations of the seniors negatively. The representations of seniors by the young viewers became closer to the representations of themselves as seniors in the future. The gender differences right after the movie became more distinct and women revealed higher sensitivity. The representations became more negative after the movie, but that effect was not a long-term for the majority of the scales. The current issue demonstrated the importance of complex approach toward predicting the influence of the cinema.